1989
DOI: 10.1128/jcm.27.5.1132-1134.1989
|View full text |Cite
|
Sign up to set email alerts
|

Gardnerella vaginalis bacteremia from pulmonary abscess in a male alcohol abuser

Abstract: A case of Gardnerella vaginalis bacteremia is reported. This bacteremia occurred in a male alcohol abuser who developed definite signs of pulmonary abscess and empyema. Streptococcus milleri grew from another blood culture, but Gardnerella vaginalis was also isolated from a bronchoscopic aspirate and pleural drainage sample as part of mixed flora containing anaerobes, Streptococcus species, Neisseria sicca, and a Haemophilus sp. We discuss the possible pathogenic character of G. vaginalis outside the genital t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…A lung abscess, empyema, and bacteremia developed in a male alcohol abuser following inhalation pneumonia; G. vaginalis in pure culture was isolated from blood and mixed with other bacteria in cultures of a bronchoscopic aspirate and pleural drainage (124). A vaginal abscess, Bartholin gland abscesses, puerperal abscess, and abdominal incisions were the sources of G. vaginalis studied by Malone et al (133).…”
Section: Suppurative Lesionsmentioning
confidence: 97%
See 1 more Smart Citation
“…A lung abscess, empyema, and bacteremia developed in a male alcohol abuser following inhalation pneumonia; G. vaginalis in pure culture was isolated from blood and mixed with other bacteria in cultures of a bronchoscopic aspirate and pleural drainage (124). A vaginal abscess, Bartholin gland abscesses, puerperal abscess, and abdominal incisions were the sources of G. vaginalis studied by Malone et al (133).…”
Section: Suppurative Lesionsmentioning
confidence: 97%
“…Smith (211) observed that cultures on vaginalis agar (V agar; see below) exhibited many short rods that were gram negative, whereas the cells were more pleomorphic, clumped, gram variable, and beaded on a medium containing starch, a fermentable compound. G. vaginalis growing in 48-h cultures of patients' blood specimens were reported as predominantly gram positive (124,245). The organism was partially or entirely gram positive in the early exponential growth phase on the inspissated serum medium of Loeffler (174) or Roux (249).…”
Section: Identification and Characteristics Of G Vaginalismentioning
confidence: 99%
“…While balanitis is usually caused by Candida organisms, anaerobes with mixed species, including G. vaginalis, were found to be the culprit in some cases [20]. Bacteremia due to G. vaginalis has been reported in men with immunosuppression, chronic alcohol use disorder, urethral stenting, meatal strictures, infected urinoma, prostate adenomas, or transurethral prostatectomy [21][22][23][24][25][26][27][28][29][30]. In two otherwise healthy patients, G. vaginalis bacteremia was found in a male presenting only with urethritis, raising the question of whether G. vaginalis is overlooked, and another with only a positive urine culture [31,32].…”
Section: Gardnerella Vaginalis Male Infectionsmentioning
confidence: 99%
“…They are generally considered to be part of the commensal microflora of various body sites, including the mouth and genitourinary and gastrointestinal tracts (Ruoff, 1988). They are frequently associated with purulent infections of the internal organs, including the liver, brain and lungs (Bateman et al, 1975;de Louvois, 1980;Legrand et al, 1989). In the oral cavity, members of the anginosus group of bacteria have been repeatedly isolated from odontogenic abscesses (Fisher & Russell, 1993;Robertson & Smith, 2009).…”
Section: Introductionmentioning
confidence: 99%